FRAUDULENT FINANCIAL REPORTING ON PROPERTY, REAL ESTATE, AND BUILDING CONSTRUCTION COMPANIES - Anik Mega Cahyani; Elva Nuraina; Farida Styaningrum (Universitas PGRI Madiun, 2021)
ABSTRACTThe purpose of this research is to detect fraudulent financial reporting in the property, real estate, and building construction sectors listed on the IDX based on the perspective of the fraud pentagon theory. The data collection technique used purposive sampling and data analysis using logistic regression. The results indicate that external pressure factors, ineffective monitoring, quality of external auditors, auditor turnover, rationalization proxied by auditor opinion, change of directors, and political connections affected FFR. Meanwhile, financial target factors, financial stability, institutional ownership, and the frequency of the appearance of the CEO image in the annual report do not affect FFR.ABSTRAKPenelitian ini bertujuan untuk mendeteksi kecurangan pelaporan keuangan pada sektor properti, real estate, dan konstruksi bangunan yang terdaftar di BEI berdasar perspektif teori fraud pentagon. Pengumpulan data menggunakan teknik purposive sampling dan analisis data menggunakan regresi logistik. Hasil penelitian menunjukkan bahwa faktor tekanan eksternal, pengawasan yang tidak efektif, kualitas auditor eksternal, pergantian auditor, rasionalisasi yang diproksikan dengan opini auditor, pergantian direksi, dan hubungan politik berpengaruh terhadap FFR. Sedangkan faktor target keuangan, stabilitas keuangan, kepemilikan institusional, dan frekuensi kemunculan gambar CEO dalam laporan tahunan tidak berpengaruh terhadap FFR.